Influence of the Type of Load on Characteristics of a Dedicated USB PD Charging System—A Case Study - Przemysław Ptak; Tadeusz Lorkowski; Krzysztof Górecki (Applied Sciences)
This paper presents the results of an experimental study on the charging process of selected mobile device batteries using a dedicated charging system operating in the Universal Serial Bus Power Delivery (USB PD) mode. The charging circuit was developed in the Flyback topology using a power factor correction (PFC) circuit. A block diagram of the charging system under consideration and a block diagram of the measurement set-up are presented. Power resistors with different resistance values and two selected mobile devices with different built-in battery capacitances were used as the load of the charging system under test. The test results are presented as a function of load resistance and the State of Charge (SoC) level of the batteries used. The measurement results obtained are discussed.